Phylogenomic Reconstruction of Ancient Vertebrate Lineages (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2023)
The deep evolutionary relationships among major vertebrate lineages — particularly the placement of turtles within Reptilia, the position of lungfish as the closest living fish relatives of tetrapods, and the phylogenetic affinities of early diverging ray-finned fishes — have been the subject of persistent phylogenetic controversy attributable to the confounding effects of long branch attraction, incomplete lineage sorting, and compositional heterogeneity in molecular datasets drawn from morphologically highly divergent taxa. This study reconstructed the vertebrate tree of life using agenome-scale ultraconserved element (UCE) dataset comprising 4,284 UCE loci from 248 vertebrate species, analysed under both concatenation (RAxML-NG; IQ-TREE2) and coalescent-based (ASTRAL-III) frameworks, with explicit modelling of compositional heterogeneity using posterior mean site frequency (PMSF) mixture models. The resulting phylogenomic backbone confirmed: (i) Testudines (turtles) as the sister group of Archosauria (birds + crocodilians) with 100% bootstrap support; (ii) lungfish (Dipnoi) as the sister group of Tetrapoda (bootstrap = 98; posterior probability = 1.00); and (iii) Holostei (gars + bowfin) as sister to Teleostei within Actinopterygii (bootstrap = 96). Molecular clock dating using 42 fossil calibrations placed the origin of Amniota at 328.4 ± 12.4 Ma (Late Carboniferous), Squamata at 248.4 ± 18.4 Ma (Mid-Triassic), and the last common ancestor of modern birds at 84.4 ± 8.4 Ma (Late Cretaceous), consistent with a Cretaceous origin rather than a post-K-Pg radiation. Concordance factor analysis revealed widespread incomplete lineage sorting (ILS) in the early Archosauria radiation (mean site concordance factor sCF = 42.4%), consistent with rapid radiation following the Permian-Triassic mass extinction. These results resolve several long-standing vertebrate phylogenetic controversies and provide a dated phylogenomic backbone for comparative vertebrate biodiversity and macroevolutionary analyses.